Pendampingan Guru Dalam Membantu Siswa Kelas V dan VI Untuk Memahmi Soal PAI di SD Negeri Bringinan Ponorogo - Fuad Khoirul Anwar; Fransiska Dyah Anggraini; Ghifari Wildan Muchlisin; Hanifah Abiyyu Khairunnisa; Hafidhul Hakim; Himatul Uliya; Nurul Malikah (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
The purpose of this study is to describe, First, the ability of students at SD Negeri Beringin in understanding the bad luck of PAI. Second, the application of mentoring carried out by teachers at SD Negeri Bringinan in helping students understand PAI questions, Third, the implications of mentoring for students in understanding PAI questions. This type of research is a case study with a descriptive qualitative approach. The data source, in the form of primary and secondary data, primary data was obtained from the results of interviews with Mrs. Paitun, S.Pd.I as a teacher of PAI subjects at SD Negeri Beringinan, while secondary data was obtained from the results of scientific studies in the form of books, journals, and other types of scientific works related to the focus of the research. The data collection technique uses interview, observation, and documentation techniques, then analyzed using Miles and Huberman's theory. The results of this study are First, the ability of students to understand the pie problem in elementary school is still lacking, many students are still confused and have difficulty in understanding the pie problem, so they do not know how to answer it. Second, the assistance provided by teachers at SD Negeri Bringinan is an initial analysis of sisiwa's ability, personal approach, appreciation and motivation. Third, mentoring activities for students have a significant influence on students involved in the mentoring process.